Development and Airworthiness Certification of the Ti6Al4V Inlet Casing Inner Forging - P, Vignesh; KV, Praveen; S, Krishna kumar; CM, Bhuvaneswari; Kale, Shirish; T, Ram Prabhu (Defence Science Journal, 2023)
The inlet casing inner has manufactured using Ti-6Al-4V alloy through a closed die-forging route. It undergoes cyclic loads in addition to operating in extreme conditions in high-temperature environments. The demanding mission requirement of these engines necessitates the inlet casing inner to be flawless throughout its life cycle while retaining its structural integrity. It makes the qualification for airworthiness of the casing, a daunting task. In addition, the qualification tests also help to evaluate the design and manufacturing processes (closed die forging) of the inlet casing inner. The tests also provide data for further improvement of the inlet casing inner in terms of strength and fatigue life. It helps to ensure that the inlet casing inner will be able to perform as expected throughout its operational life. All the batch and consolidated test results comply with the relevant ASTM, MIL standards, and test schedule requirements.